2018
DOI: 10.1371/journal.pone.0202384
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone pretreatment impairs the thymidylate synthase inhibition mediated flare in thymidine salvage pathway activity in non-small cell lung cancer

Abstract: IntroductionSuccessful inhibition of thymidylate synthase (TS) by pemetrexed, a TS inhibitor, results in a reproducible transient burst or “flare” in thymidine salvage pathway activity at 2 hrs. of therapy which can be measurable with FLT-PET ([18F]fluorothymidine-positron emission tomography) in non-small cell lung cancer (NSCLC). Routine administration of dexamethasone with pemetrexed-based therapy could potentially confound this imaging approach since dexamethasone is known to inhibit expression of thymidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…According to two complementary cell viability assays, cisplatin displayed a concentration-and time-dependent cytotoxic effect with IC50 values ranging from approximately 10 to 16 µ M for 72 h, being more than two-fold higher for a shorter incubation period of 48 h. Considering the results available in the literature, the effect of cisplatin in H1975 cells viability herein obtained is comparable to those described by other authors using different methodologies such as sulforhodamine B assay (IC50 = 8.31 µ M [27]) and MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay (IC50 = 6.71 µ M [42] and IC50 = 11 µ M [43]) for the same 72 h incubation period. As for 48 h of cisplatin incubation in the same cell line, our results differ from the study of Zhao et al [44] that found an IC50 value of 3 µ M using the MTT assay.…”
Section: Discussionsupporting
confidence: 87%
“…According to two complementary cell viability assays, cisplatin displayed a concentration-and time-dependent cytotoxic effect with IC50 values ranging from approximately 10 to 16 µ M for 72 h, being more than two-fold higher for a shorter incubation period of 48 h. Considering the results available in the literature, the effect of cisplatin in H1975 cells viability herein obtained is comparable to those described by other authors using different methodologies such as sulforhodamine B assay (IC50 = 8.31 µ M [27]) and MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay (IC50 = 6.71 µ M [42] and IC50 = 11 µ M [43]) for the same 72 h incubation period. As for 48 h of cisplatin incubation in the same cell line, our results differ from the study of Zhao et al [44] that found an IC50 value of 3 µ M using the MTT assay.…”
Section: Discussionsupporting
confidence: 87%
“…FLT-PET imaging provides additional validation of arginine auxotrophic thoracic cancers, especially MPM, in which there are several resistance mechanisms, including ASS1 re-expression (i.e., recycling of citrulline to arginine), autophagy, and metabolic support by macrophages and other stromal cells, which affect subsequent disease progression. 31 …”
Section: Discussionmentioning
confidence: 99%
“…FLT-PET imaging provides additional validation of arginine auxotrophic thoracic cancers, especially MPM, in which there are several resistance mechanisms, including ASS1 reexpression (i.e., recycling of citrulline to arginine), autophagy, and metabolic support by macrophages and other stromal cells, which affect subsequent disease progression. 31 Early phase combination trials of ADI-PEG 20 with chemotherapy are reporting increased efficacy, owing to synergistic and additive mechanisms of cytotoxicity in various cancer types, accompanied by more sustained arginine depletion with the slower emergence of anti-ADI-PEG 20 antibodies. 13,[32][33][34] In thoracic cancers, this multimodality strategy has progressed to a randomized phase 3 study of ADI-PEG 20 (or placebo) PemCis focusing on chemorefractory (nonepithelioid) MPM which is expected to report final results in 2022 (ATOMIC-meso, ClinicalTrials.gov identifier: NCT02709512).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is an ongoing study to evaluate 18F-FLT uptake in non-small cell lung cancer following pemetrex treatment. Because of the response and activation of the dexamethasone/pemetrexed thymidine salvage pathway inhibited by dexamethasone/pemetrexed [132], the authors hypothesize that this strategy can be detected as an increase in FLT tumor uptake that subsequently decreases with reduced proliferation. In this study, the FLT response had a good overall survival rate that was twice that of no response.…”
Section: Thymidinementioning
confidence: 99%